Stress ecology in times of global change – single and combined effects of ocean acidification, temperature and food availability on different life stages of the barnacle Amphibalanus improvisus - Pansch, Christian (2012)
Increasing atmospheric CO2 affects seawater pH and chemistry. This process, commonly known as ocean acidification (OA), has led to a decrease in oceanic seawater pH by 0.1 since the industrial revolution. Oceanic models show that mean pH may fall from the current 8.1 units to 7.8 and 7.5 by 2100 and 2300, corresponding to levels of about 1000 and 2000 µatm pCO2, respectively. Coastal habitats have been described to differ substantially from open ocean conditions. Not only absolute mean values and annual or daily fluctuations but even future predictions differs considerably from open ocean norms. These characteristics evolved over many years and likely formed species or populations, which are more robust to future OA than species or populations from more stable oceanic environments. Calcifying species as well as early life-history stages of marine organisms are considered to be mainly affected by OA. The acorn barnacle Amphibalanus improvisus is a dominant marine calcifier within the western Baltic Sea and has a complex life cycle with various stages such as feeding nauplii and non-feeding cyprids as well as settled calcifying juveniles. Thus, this species is an ideal organism to address a wide range of hypotheses. In this thesis, I investigated the sensitivity of the A. improvisus towards OA stress in combination with additional environmental parameters such as temperature and food availability. The organisms for this study came from the Kiel Fjord, Germany and the Tjärnö Archipelago, Sweden, which, to a certain extent, allows interpretations on the population level. As one of the first cases, this study evaluates the entire life cycle of an invertebrate towards OA in combination with additional stressors. Nauplius larvae of A. improvisus were affected neither by moderate (<1500 µatm pCO2) nor by severe (>1500 µatm) OA under summer temperature conditions of 20 °C in the Kiel population or under slightly elevated temperatures (25 °C) in the Tjärnö population. However, in cooler waters (12 °C) severe OA ...